The effect of trade openness on optimal government size under endogenous firm entry - Sandra Hanslin (University of Zurich, Socioeconomic Institute, 2008)
This paper analyzes the effect of trade liberalization on government spending in a general equilibrium model with a continuum of industries supplying tradable and nontradable goods under monopolistic competition. Trade liberalization is modeled as the opening up of product markets between two countries, which may differ in total factor productivity, factor endowment and fix cost technology. In this setup, I show that the optimal provision of a public consumption good depends positively on the degree of openness. Moreover, the richer and more productive country chooses a lower optimal government share.
Keywords: F12; H40; F15; 330; international trade; monopolistic competition; trade openness; public expenditure; Handelsliberalisierung; Öffentliche Ausgaben; Allgemeines Gleichgewicht; Monopolistischer Wettbewerb; Theorie